Modeling the hydrodynamics of heap leaching in sub-zero temperatures. (1st May 2016) - McBride, D.; Gebhardt, J.E.; Croft, T.N.; Cross, M.
Highlights: Comprehensive heap leach model captures diverse hydrodynamic conditions. Model allows for thermo-fluid–solid reactions and sub-zero hydrodynamic conditions. A gold oxide 'test' heap is simulated for seasonal above- and sub-zero temperature. The results demonstrate how recovery is affected by thermo-hydrological changes. Abstract: Heap leaching involves the application of a leach solution onto stacked low grade ores. Solution percolates through the ore, dissolving metals from various minerals, and is recovered at the base. This process is conceptually a simple one, but quickly becomes complex when considering the sub-processes, such as dissolution chemical reactions, oxidation, precipitation, ore with different leaching characteristics, and multi-lift heaps with dynamically changing irrigation schemes. In addition, changing meteorological conditions, such as heavy rain, evaporation and extreme ambient temperatures have a significant effect on the hydrodynamics. Various factors, such as large variations in ore hydraulic properties, saturated–unsaturated flow, preferential flow pathways, perched water tables, infiltration into dry ore or possible freezing of solution within the heap, can lead to reduced leaching efficiency. This contribution describes the methods employed within a computational fluid dynamics heap leach model to account for freezing climate conditions. Validation of one-dimensional thermal phase change is performed and a theoretical column of coarse and fine ore is partially frozen to illustrate how the preferred flow path can be counter-intuitive. Finally, a three-dimensional heterogeneous gold oxide 'test' heap is simulated assuming non-thermal reactions and sub-zero ambient temperatures. The results demonstrate how recovery can be affected by cold weather changing the hydrodynamics of the heap.